KEMAMPUAN PEMECAHAN MASALAH DAN BERFIKIR KRITIS SISWA MELALUI MODEL PROBLEM BASED LEARNING DI SDN 106232 PENGGALANGAN - Gurning, Parida Herianti; Hasratuddin; Puryati; Siregar, Syahril (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low mathematics learning outcomes of fifth-grade students at SD Negeri 106232 Penggalangan, which are believed to stem from weak critical thinking and problem-solving skills. The purpose of this research was to evaluate the effectiveness of the Problem Based Learning (PBL) model in enhancing these two competencies. A quantitative approach was employed using a quasi-experimental method, involving two groups: an experimental class taught using the PBL model and a control class receiving conventional instruction. A total of 42 students were selected as samples through total sampling from both classes. The research instruments consisted of validated tests measuring critical thinking and problem-solving abilities. Data were analyzed using a two-way ANOVA test. The findings revealed a significant difference between the two groups, with students in the experimental class demonstrating higher levels of critical thinking and problem-solving skills. Furthermore, an interaction was found between the learning model and students’ initial mathematical ability in influencing learning outcomes. The study concludes that the Problem Based Learning model is effective in improving elementary school students’ critical thinking and problem-solving skills and can serve as an innovative instructional strategy